FIGURES OF POLITICAL INCORECTNESS – SOCIOPOLITICAL MYTHS AND SYMBOLS IN MIODRAG BULATOVIĆ’S WORK - Szukalska, Aldona (Porównania, 2013)
‘Figures of Political Incorectness – Sociopolitical Myths and Symbols in Miodrag Bulatović’s work’ this is an article dedicated to literary output of the Serbian author with Montenegrin background and in particular to his individual symbolism from so called exile trilogy which comprises of three novels: Men of four fingers, Gullo Gullo, Peti Prst. With their help the author is dealing with the Mideast sociopolitical myths and also the myth of ‘The Great Slavism’. Vampire Dracula, Pig Josephine, Eagle Georg, Dog Zdeniek and animal Gullo Gullo are from one end symbols invented by the author and intentionally intruding political correctness and from the other they are allowing him to create new myths which are explaining the fatalism of Slavic people’s history.